1995
DOI: 10.1093/infdis/172.4.974
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Human Peripheral Blood Mononuclear Cell Engraftment and Enhanced Susceptibility to Human Immunodeficiency Virus Type 1 Infection in NOD/LtSz-scid/scid Mice

Abstract: Inbred C.B-17-scid/scid mice accept human peripheral blood mononuclear cell (PBMC) xenografts and are susceptible to human immunodeficiency virus type 1 (HIV-1) infection, but low levels of PBMC engraftment impede use of this system in HIV research. This report describes the effect of host strain background on human PBMC engraftment and HIV infectivity in scid mice. Back-crossing the scid mutation to the NOD/Lt strain (designated NOD/LtSz-scid/scid) increased the percentage of engrafted human PBMC in recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
119
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(124 citation statements)
references
References 52 publications
4
119
1
Order By: Relevance
“…Three, 4, and 8 wk after HIV-1 infection, mice were killed and blood and spleen samples were collected. The samples were analyzed for percentages of human CD45 ϩ cells by flow cytometry and for the presence of HIV-1 DNA and RNA by PCR, as previously described (1,36). Spleen cell samples for flow cytometry were analyzed with the panel of human mAb used for the PBMC-engrafted mice described above.…”
Section: Hiv-1 Infection Of Pbmc-engrafted Micementioning
confidence: 99%
See 2 more Smart Citations
“…Three, 4, and 8 wk after HIV-1 infection, mice were killed and blood and spleen samples were collected. The samples were analyzed for percentages of human CD45 ϩ cells by flow cytometry and for the presence of HIV-1 DNA and RNA by PCR, as previously described (1,36). Spleen cell samples for flow cytometry were analyzed with the panel of human mAb used for the PBMC-engrafted mice described above.…”
Section: Hiv-1 Infection Of Pbmc-engrafted Micementioning
confidence: 99%
“…It is unknown which specific innate immune defect, or combination of defects lead to enhanced engraftment with high levels of human hematolymphoid cells. Markedly decreased levels of human lymphoid cell engraftment are associated with increased levels of innate immunity in other strains of scid mice (1,12). Based on our published data, NODLtSz-scid mice are now the strain of choice for most laboratories studying engraftment of human hematolymphoid cells in immunodeficient mice (1, 8 -10, 13-18).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Nonobese diabetic (NOD)/SCID mice exhibit reduced NK activity, macrophage function and serum hemolytic complement activity in addition to the deficit in mature T and B cells [24,25]. Although increased huT cell engraftment levels and X-GVHD have been reported for NOD/SCID mice, these mice are still constrained by the presence of residual NK cell activity and poor human CD4 + T cell engraftment [23,24,[26][27][28][29][30]. Recently, this residual NK cell activity was virtually eliminated by backcrossing the β 2 -microglobulinnull (β2m null ) allele onto the NOD/SCID background [31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, immunodeficiency mutations on the nonobese diabetic (NOD) mouse background support higher engraftment levels of human hematopoietic cells and immune cells as compared to other backgrounds, such as BALB/c, C3H and C57BL/6. [30][31][32][33][34][35] The NOD mouse background offers a number of genetic advantages that promote the engraftment of human immune systems. 34 A direct comparison of immunodeficient IL2rc null mice on either a NOD background (NOD-scid IL2rc null (NSG) and NOD-Rag1 null IL2rc null (NRG)) or BALB/c (BALB-Rag2 null IL2rc null ) background revealed that the NOD background supported significantly higher levels of human cell engraftment following injection of human HSC.…”
Section: Strain Development For Humanized Micementioning
confidence: 99%